Simulation of an On-grid Wind-Hydrogen Coupling System (Case Study: Mollo Selatan Subdistrict, Indonesia) - Abdul Goffar Al Mubarok; Tian De (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2022)
This study proposed a wind-hydrogen coupling systems control strategy to investigate its feasibility. The control strategy regulates the electrical energy generated by a wind turbine to meet the domestic load demand of a specific site. The remaining electrical energy is regulated to supply electrolyzer for producing hydrogen as energy storage. The stored energy in the form of hydrogen can be reconverted into electricity by utilizing fuel cells to meet the domestic load demand. Selecting proper sites for evaluating the control strategy is critical. Hence this study also conducts a wind resource assessment approach that considers the humidity effect to wind power density, wind turbine power curve, and annual energy production of a wind turbine. This approach achieved a better precise annual energy production estimation than other approaches that neglect the humidity. Proper wind resource assessment resulted in a site for the case study, Mollo Selatan Subdistrict for an on-grid system. The control strategy was modeled and evaluated with MATLAB Simulink. The simulation results show the possibility of storing energy generated by the wind into hydrogen and meeting the load demand of the case study location.